The Narratives of Marginalized Women in Samar, Philippines: A Baseline Study for Extension Program Sustainability - Gatil, Tranie B.; Cinco, Mary Jane B.; Acosta, Nathalie Ann A.; Baclay, Joan J. (Journal of Natural Language and Linguistics, 2024)
With the alarming poverty incidence among families in Samar Province at 27% (PSA, 2021), Samar State University conducted an extension program along entrepreneurship engagement among marginalized families. To better improve the program, an impact assessment was conducted. This study assessed the impact of the capacity building on developing entrepreneurial mindset among marginalized families in Samar. A focus group discussion (FGD) was conducted with the program beneficiaries from Marabut and Basey, Samar. Through Moustaka’s (1994) structured method of inductive data analysis, the following themes were identified: Positive attitude and mindset is a requisite to successful entrepreneurship; entrepreneurial knowledge dictates readiness towards entrepreneurship, and; lack of fund impedes entrepreneurial intention. The program was successful in its goal of educating the marginalized families of the significant role entrepreneurial mindset and positive communication play in a successful entrepreneurship pursuit. However, lack of capital to start business is seen as a major impediment. To remedy this, inclusion of financial literacy and entrepreneurial management courses in the program is recommended. Finally, to improve the andragogy, crafting of learning material in mother tongue is recommended.